Simvastatin exerts anticancer effects in osteosarcoma cell lines via geranylgeranylation and c-Jun activation - Kany, Shinwan; Woschek, Mathias; Kneip, Niels; Sturm, Ramona; Kalbitz, Miriam; Hanschen, Marc; Relja, Borna (International Journal of Oncology, 2018)
Osteosarcoma is the leading primary bone cancer in young adults and exhibits high chemoresistance rates. Therefore, characterization of both alternative treatment options and the underlying mechanisms is essential. Simvastatin, a cholesterol-lowering drug, has among its pleiotropic effects anticancer potential. Characterizing this potential and the underlying mechanisms in osteosarcoma is the subject of the present study. Human osteosarcoma cells (SaOS-2 and U2OS) were treated with simvastatin (4-66 μM) for 48 or 72 h. The effects of downstream substrate mevalonate (MA) or substrates for isoprenylation farnesyl pyrophosphate (FPP) and geranylgeranyl-pyrophosphate (GGPP) were evaluated using add-back experiments. Tumour growth using MTT assay, apoptosis, cell cycle and signalling cascades involved in simvastatin-induced manipulation were analysed. The results revealed that simvastatin dose-dependently inhibited cell growth. Simvastatin significantly induced apoptosis, increased the Bax/Bcl-2 ratio, and cleavage of caspase-3 and PARP protein. Simvastatin impaired cell cycle progression as shown by significantly increased percentages of cells in the G0/G1 phase and lower percentages of cells in the S phase. Gene expression levels of cell cycle-regulating genes (TP53, CDKN1A and CDK1) were markedly altered. These effects were not completely abolished by FPP, but were reversed by MA and GGPP. JNK and c-Jun phosphorylation was enhanced after simvastatin treatment, while those were abolished when either MA or GGPP were added. In conclusion, simvastatin acts primarily by reducing prenylation to induce apoptosis and reduce osteosarcoma cell growth. Particularly enhanced activation of c-Jun seems to play a pivotal role in osteosarcoma cell death.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Cancer; Geranylation; JNK; Osteosarcoma; Prenylation; Rho proteins; Statin